Mobile money innovations and health performance in sub-Saharan Africa - Simplice Asongu; Yolande E. Ngoungou; Joseph Nnanna (African Governance and Development Institute (AGDI), 2023)
This study assesses nexuses between mobile money innovations and health performance in terms of total life expectancy in 43 countries in Sub-Saharan Africa employing data for the period 2004-2018. Four mobile money innovation dynamics are proxied with registered mobile money agents and active mobile money agents. The empirical evidence is based on quantile regressions. The findings overwhelmingly show that mobile money innovations are relevant in improving health performance or total life expectancy exclusively in bottom quantiles of the conditional distribution of total life expectancy. In other words, countries with below-median levels of total life expectancy are more susceptible to benefit from mobile money innovations compared to countries with above-median levels of total life expectancy. It follows that common or general policy measures on the linkage between mobile money innovations and health performance are unlikely to succeed unless attendant policies are contingent on initial levels of health performance and hence, tailored differently across countries with various initial levels of health performance. More policy implications are discussed.
Keywords: O40; G20; I10; I32; I20; 330; Mobile phones; financial inclusion; health; sub-Saharan Africa